Analysis Of Aggregate Planning To Streamline Production Cost In The Mahakam Ice Crystal Home Industry In The City Of Palangka Raya: - Mukmin Effendi; Hansly Tunjang; Deddy Rakhmad Hidayat; Ina Karuehni (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Purpose - This study aims to obtain an aggregate planning strategy or alternativethat can be applied to the Mahakam Ice Crystal home industry and how much is thecost efficiency of the resulting production.Design/methodology/approach - The type of research used in this study isdescriptive analytical using a quantitative approach with the POM-QM for WindowsV5 analisis analysis tool.Findings - Based on the results of research and calculation of the total cost ofaggregate planning, Chase Strategy was chosen as a strategy or alternative foraggregate planning with the lowest production cost value of Rp. 97.371.000,- andcan streamline production costs by 17,3% of the total production costs of theMahakam Ice Crystal Home Industry.